Gut microbiota and type 1 diabetes: a two-sample bidirectional Mendelian randomization study - Luo, Manjun; Sun, Mengting; Wang, Tingting; Zhang, Senmao; Song, Xinli; Liu, Xiaoying; Wei, Jianhui; Chen, Qian; Zhong, Taowei; Qin, Jiabi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The real causal relationship between human gut microbiota and T1D remains unclear and difficult to establish. Herein, we adopted a two-sample bidirectional mendelian randomization (MR) study to evaluate the causality between gut microbiota and T1D. Methods We leveraged publicly available genome-wide association study (GWAS) summary data to perform MR analysis. The gut microbiota-related GWAS data from 18,340 individuals from the international consortium MiBioGen were used. The summary statistic data for T1D (n = 264,137) were obtained from the latest release from the FinnGen consortium as the outcome of interest. The selection of instrumental variables conformed strictly to a series of preset inclusion and exclusion criteria. MR-Egger, weighted median, inverse variance weighted (IVW), and weighted mode methods were used to assess the causal association. The Cochran’s Q test, MR-Egger intercept test, and leave-one-out analysis were conducted to identify heterogeneity and pleiotropy. Results At the phylum level, only Bacteroidetes was indicated to have causality on T1D (OR = 1.24, 95% CI = 1.01-1.53, P = 0.044) in the IVW analysis. When it comes to their subcategories, Bacteroidia class (OR = 1.28, 95% CI = 1.06-1.53, P = 0.009, PFDR = 0.085), Bacteroidales order (OR = 1.28, 95% CI = 1.06-1.53, P = 0.009, PFDR = 0.085), and Eubacterium eligens group genus (OR = 0.64, 95% CI = 0.50-0.81, P = 2.84×10-4, PFDR = 0.031) were observed to have a causal relationship with T1D in the IVW analysis. No heterogeneity and pleiotropy were detected. Conclusions The present study reports that Bacteroidetes phylum, Bacteroidia class, and Bacteroidales order causally increase T1D risk, whereas Eubacterium eligens group genus, which belongs to the Firmicutes phylum, causally decreases T1D risk. Nevertheless, future studies are warranted to dissect the underlying mechanisms of specific bacterial taxa’s role in the pathophysiology of T1D.